Isla to island - Castellanos, Alexis (Atheneum Books for Young Readers, 2022)
Wordless graphic novel follows young Marisol whose Cuban parents send her to live in the United States after Fidel Castro takes power in 1961. After arriving in New York City to live with a kind, elderly couple, her cold, gray surroundings slowly turn vibrant again as she learns the language and celebrates her culture through food and music.